They called it democracy? The aesthetic politics of the Spanish transition to democracy and some collective hijackings of history after the 15M movement - Labrador Méndez, Germán (Historein, 2015)
This article studies the imaginaries of political change available during the Spanish transition to democracy (1973–1982) and their new political usages by the Spanish 15M Occupy movement in the context of the 2008–2014 economic crisis. I argue that protesters are now rediscovering the old symbols used against Franco’s dictatorship and adapting them to the new political circumstances, through graffiti, slogans, artistic performances and other ephemeral materials.